220 RELATIONSHIP BETWEEN HEIGHT AND SYSTOLIC BLOOD PRESSURE IN OLDER ADULTS. (25th October 2022) - Morrison, L; Chen, H; Sheehy, T; Costelloe, A; Griffin, M; Quinn, C; O'Connor, M; Peters, C; Lyons, D
Abstract: Background: Hypertension is common amongst older adults in Ireland and is a major risk factor for both ischaemic and haemorrhagic stroke. Several studies have investigated the relationship between height and hypertension, however results have been inconsistent. In our Irish tertiary hospital patients undergoing tilt table testing have resting blood pressure measured prior to the test, and height recorded. Our aim was to assess whether there is a relationship between height and resting Systolic Blood Pressure (SBP) in patients aged over 60 years. Methods: All tilt table test results between 2000 and 2021 in a single centre were reviewed retrospectively, collecting data on age, height and resting SBP. Any incomplete records were excluded, as were those from patients under 60 years old. Linear regression modelling was used to assess relationship between height and resting SBP. Results: A total of 4, 729 complete records were included for patients over 60 years old. 2630 (61.5%) of the patients were female. Mean age was 77 ± 7.8 years. 57.7% patients had either an elevated resting systolic and/or diastolic BP ≥130/80 and 28.4% ≥140/90. The linear regression model established that while height could be used to predict resting systolic blood pressure (beta=-0.166, 95% CI: –0.219 to –0.113, p<0.001), height only accounted for 0.8% of variability in resting SBP (R 2 = 0.008). Conclusion: Our large dataset establishes an association but no meaningful causation between height and resting systolic blood pressure. Current antihypertensive treatment was not recorded, which may have affected the results. Future studies will include further multivariate analysis accounting for antihypertensive use and other factors that may impact hypertension such as age, weight and gender.